(untitled) (Journal of Engineering, 2024)
The aim of the present work is to study the controlling of weld defects and dimensions by using robot cell which associated with MIG/MAG welding process. The base metal is evaluated through the chemical analysis, mechanical tests and micro-structure tests, filler metal is also selected and analyzed according to AWS specification. The various welding conditions are chosen to be as suitable as possible such as welding current, arc voltage, travel speed, stick out, protective gases and there is another effective parameter called as torch inclination angles, which has an obvious effect on the weld bead dimensions. Robotic arc welding has been applied and analyzed for the welding of a complex sheet metal product named as product X-11. The product X-11 required 33 are welds with total length of (182.8 cm) of welds. Two complete weld programs development are carried out. The weld program consists of two stages, which are the front side and the back side. The cycle time calculates for each program. It is obvious that the productivity is increase to about 186%. Some of quality control tests are curried out for the purpose of improving in weld quality. Some of inspections and tests are achieved for finding out the defects in the weldments in the mass production which is considered as attributes data. Pareto diagram is also set up to show the important defects in the production. The presence of defects in the final products may belong to many factors (eg. poor fits for welding parts, impurity of protective gases, etc.),